Catira: performance e tradição na dança caipira - Marra, Juliana Ribeiro (2016)
This research aims at proposing a widening of the understanding of catira, a traditional dance of the Brazilian popular culture. The dance territorializes itself in the region of the caipira culture and has its structure founded in the clapping of hands and on step dancing of the dancers under the rhythm of the moda de viola and of the recortado. The viola is therefore the essential instrument for the dance. Catira is a dance but also music and poetry, which find identification with the rural world of the southern center of Brazil. Although the practice is considered contemporary of the country´s colonization – and the catira groups are many – there are few records and studies that go about it. Therefore, initially to introduce the dance, its forms and elements were presented and there has been an attempt to analyze them bearing in mind its insertion in the studies concerning popular culture and folklore in Brazil. Following that the theoretical and methodological approach of the research is outlined. Catira becomes then the focus of an analysis built within interdisciplinary knowledge. Focus in which, a method and categories of analyses of social sciences and also of the arts, are supposed. Cultural performances rise as the interpretative axis of the research, as long as in relationship with other concepts that also establish themselves in the multidisciplinary perspective – i.e. tradition, socialization, memory, body and dance. Bearing in mind these concepts, we reach the analysis of the records gained from the field research of the work. The analytical narrative is built from the interviews, observation and participation, theoretical relationships and audiovisual records, mainly the photographs taken in the fieldwork. Firstly the dance of the catira within the ritual of folia of Companhia de Reis Bandeira Vermelha, in the town of Goiás/GO, is analyzed. After that the focus is turned to the town of Itaguari/GO and its enormous Folia de Reis, where the groups Irmãos Oliveira e Orgulho Caipira are to be found. Finally having the experience lived with the groups as a referential, the analysis is deepened with focus on the identities, the power relationships and the negotiating carried by the groups of catira. The understanding is that the identities sought and lived are related to the places and territories in which this performing heritage of the caipira culture takes place. The endurance is characteristic of these bodies that move harmonized and in pairs since immemorial times, in the conjunctures of nowadays – if permitted indicating a path beforehand – in a future not envisioned.